Metagenomic Next-Generation Sequencing vs. Traditional Microbiological Tests for Diagnosing Varicella-Zoster Virus Central Nervous System Infection - Zhu, Yunqi; Xu, Miaomiao; Ding, Chengyuan; Peng, Zhihang; Wang, Weixiao; Sun, Binghu; Cheng, Jian; Chen, Chen; Chen, Wei; Wei, Hongxia; Hu, Zhiliang (Frontiers in Public Health, 2022)
Background: Unbiased metagenomic next-generation sequencing (mNGS) detects pathogens in a target-independent manner. It's not well understood whether mNGS has comparable sensitivity to target-dependent nucleic acid test for pathogen identification. Methods: This study included 31 patients with chickenpox and neurological symptoms for screening of possible varicella-zoster virus (VZV) central nervous system (CNS) infection. Microbiological diagnosing of VZV CSF infection was performed on stored cerebrospinal fluid (CSF) samples using mNGS, quantitative and qualitative VZV-specific polymerase chain reaction (PCR) assays, and VZV IgM antibodies test. Results: The median age was 30.0 (interquartile range, 24.3-33.3) years. 51.6% of the patients were male. 80.6% of the patients had normal CSF white blood cell counts (≤ 5×106/L). VZV IgM antibodies presented in 16.1% of the CSF samples, and nucleic acids were detectable in 16.1% and 9.7% using two different VZV-specific real-time PCR protocols. Intriguingly, maximal identification of VZV elements was achieved by CSF mNGS (p=0.001 and p=007; compared with qualitative PCR and VZV IgM antibody test, respectively), with sequence reads of VZV being reported in 51.6% (16/31) of the CSF samples. All VZV PCR positive samples were positive when analyzed by mNGS. Of note, human betaherpesvirus 6A with clinical significance was unexpectedly detected in one CSF sample. Conclusions: Our study suggests that CSF mNGS may have higher sensitivity for VZV detection than CSF VZV PCR, and has the advantage of identifying unexpected pathogens.